PAKISTANI WOMEN'S RESISTANCE TOWARD PATRIARCHAL, CULTURE IN QAISRA SHAHRAZ'S NOVELS; THE HOLY WOMAN AND TYPHOON - Seswita Seswita (Universitas Negeri Padang, 2015)
Feminist movement has started to arise in the whole world in this twentieth century. Women are trying to voices their rights by struggling to fight for patriarchy. the system in which women are considered inferiorand helpless. In different part of the world we still can see discrimination toward women in every field; social life, education. domestic life, law, and many more. Due to the discrimination thing, the feminist try to struggle in every way and one of them is through literature. There are so many novels written by female authors, not only from western countries but also from eastern that usually discussed and talked about women struggle and image of women in specific culture depends on the author's background. Qaisra Shahraz is one of the female writer from Pakistan who live in Manchester, England since she was l0 years old. Her two novels: The Holy Women and Typhoon are mainly discussed about image of Pakistani women who try to live their life normally with dignity in the system of patriarchy. Those Pakistani women are using their image and characterization to resist against the Eastern patriarchal culture that is represented by male characters existed in the two novels.